Coordination skills in 9 to 11 years old pupils at practical elementary schools in relationship to their degree of intellectual disability [Úroveň vybraných koordinačních schopností 9-11letých žáků základních škol praktických v závislosti na stupni jejich mentálního postižení] - Alena Lejčarová (Palacky University, 2009)
BACKGROUND: The degree of pupils' intellectual disability is regarded as the fundamental criterion for a necessary internal differentiation in the physical education teaching process at practical elementary schools. Up to now, children with intellectual disability, or pupils at practical elementary schools, have not received, in this regard, so much attention, neither in the area of research nor in the teaching process. OBJECTIVE: The aim of the conducted study was to identify the level of selected coordination skills in 153 9 to 11 years old pupils at practical elementary schools in Prague in relationship to their degree of intellectual disability. METHODS: Seven tests of coordination skills (rhythmical, balance, kinaesthetic differential, alteration, and associative) were used to assess the level of coordination skills in these children. RESULTS: Substantive significant differences (using Cohen's d index) were proven, with an almost absolute definiteness, between pupils having their intellectual abilities in the lower boundary area of mild intellectual disability, and those whose intellectual abilities are in the upper boundary area of mild intellectual disability, and further between these and the others (profound intellectual substandard, mild intellectual substandard, average intellectual abilities - lower average). From the point of view of the average values of performance parameters, a direct relationship with the degree of intellectual disability can be observed - the former decreases as the latter increases. However, the best test score was surprisingly achieved by pupils with a slightly below average intellect and not by pupils with the highest level of intellectual abilities. CONCLUSIONS: Different results of practical elementary school pupils' motor tests are causally dependent not only on the level of intellectual disability, but on its aetiology, too. They are also influenced by particular characteristics of pupils' personalities (including motivation) and by the environment they live in. [VÝCHODISKA: Za jedno z hlavních kritérií nezbytné vnitřní diferenciace tělovýchovného procesu na základních školách praktických je považován stupeň mentálního postižení žáků. Doposud však dětem s mentálním postižením, resp. žákům základních škol praktických nebyl v tomto ohledu věnován dostatek pozornosti jak v oblasti výzkumného bádání, tak v tělovýchovné praxi. CÍLE: Cílem realizované studie bylo zjistit úroveň vybraných koordinačních schopností 153 žáků (ve věku 9-11 let) na základních školách praktických v Praze s ohledem na stupeň jejich mentálního postižení. METODIKA: K posouzení úrovně vybraných koordinačních schopností bylo použito sedm motorických testů (rytmické, rovnováhové, kinesteticko-diferenciační schopnosti, schopnosti přestavby a sdružování). VÝSLEDKY: Téměř naprosto jednoznačně byly věcně významné rozdíly (užitím Cohenova koeficientu d) prokázány mezi žáky s intelektovými schopnostmi v oblasti dolní hranice lehkého mentálního postižení a ostatními s výjimkou těch, jejichž intelektové schopnosti se pohybují na horní hranici lehkého mentálního postižení, a dále mezi těmito žáky a ostatními (hluboký intelektový podprůměr, lehký intelektový podprůměr, průměrné intelektové schopnosti - nižší průměr). Z hlediska průměrných hodnot motorických výkonů lze sledovat jejich přímou vazbu k míře mentálního postižení - klesají s jejím růstem. Nejlepší testová skóre byla překvapivě zaregistrována u žáků s lehkým intelektovým podprůměrem, a nikoliv u žáků s nejvyšší úrovní intelektových schopností. ZÁVĚRY: Rozdílné výsledky v motorických testech žáků základních škol praktických nejsou ryze kauzálně závislé pouze na stupni mentálního postižení, ale i na jeho etiologii. Rovněž je ovlivňují i specifika osobnosti žáků (včetně schopnosti motivace) a podmínky prostředí, v němž se pohybují.]